Inkonsistensi Penerapan Metode Skeptisisme Filosofis Descartes dalam Fī Shi‘r al-Jāhilī - Millati, Halya; Umami, Khoirul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2021)
Shi‘r jāhilī, which mainstream commentators use as a reference for Qur’anic interpretation, has drawn criticism. One of the criticisms was made by Ṭāhā Ḥusayn, who considered it irrelevant for the source of interpretation as it was created by the later Muslim community, not the pre-Islamic poets, during the caliphate period with various interests. He used Descartes’ method of philosophical skepticism to propose his critique. However at the practical level, Ḥusayn seems inconsistent in applying the method. This paper attempts to reveal the inconsistencies of Ḥusayn’s application on philosophical skepticism and to describe some of the criticisms of Muslim scholars toward his idea. Using content analysis, this paper argues that Ḥusayn does not apply philosophical analysis as like Descartes, who uses intuition and deduction in detailed manner. Unlike Descartes, who uses doubt as a method of finding the truth, Ḥusayn makes doubt as the objective. Meanwhile, the Muslim scholars reproach Ḥusayn’s lack of objectivity in his study that leads to numerous deficient argument.